Assessment of seat belt use in University of Cape Coast campus, Ghana. Issue 1 (1st January 2018) - Ogunleye-Adetona, Comfort; Ojo, Thomas; Afukaar, Francis
Abstract: The paper assesses seat belt use by vehicle occupants such as drivers, front-right passengers and two rear seat passengers in University of Cape Coast campus (UCC), Ghana. An unobstructive observational study of the seat belt wearing status, gender and age-group of motor vehicle drivers, front-right and rear seat passengers disaggregated by vehicle type and usage was carried out from 7 to 9 am and 3 to 5 pm on weekdays at the three entrances into UCC. The results revealed that 3451 drivers, 1728 front-right seated passengers, 1264 first-rear and 1176 s-rear seated passengers were successfully observed. Seat belt use by drivers, front right passengers and rear-seat passengers is 22.2, 2.4 and 1% respectively. Female drivers and female front-right passengers are more likely to wear their seat belts compared to their male counterparts ( p  < 0.001). There is an association between restrained drivers and restrained front-right seat passengers ( p  < 0.001). There is the need for concerted efforts to educate and create awareness on the safety benefits of seat belt usage and enforce the use of seat belt by the National Road Safety Commission and University Transport Committee authority so as to increase the compliance level.